Specificity and spectrum of injuries among volleyball players - Dariusz Chojęta; Barbara Maziarz; Ewelina Zygmunt; Hubert Wróblewski; Aleksandra Zimna (Kazimierz Wielki University, 2020)
Volleyball is one of the most popular sports around the world. Due to its non-contact nature, it is considered as one of the safer team sports. The specificity of contusions in volleyball players is related to the type of performed and repeated movement patterns. The aim of the study was to describe the issue of injuries among volleyball players - most common anatomical locations, mechanisms, risk factors, methods of prevention. The article was created on the basis of a literature review. The most common type of injury found in volleyball players is ankle sprain. Overuse injuries most often affect the knees and shoulders. Blocking and spiking are elements of the volleyball game most closely related to contusions. Risk factors include position / role on the court, history of previous injuries and adaptive changes in the musculoskeletal system. The basic form of prevention is education regarding the development of an appropriate game technique and correct movement patterns. An important part of the training of volleyball players should be adequate warm-up, mobilization exercises and stretching. Further research should focus on understanding more precisely and describing the etiology of injuries. This could translate into the development of specific prophylaxis in the future, especially in relation to the areas of the body of volleyball players most affected by contusions. The effectiveness of injury prevention methods should be tested by carrying out large and well-designed scientific studies to provide data with high evidence strength.